Pineal Parenchymal Tumour of Intermediate Differentiation: a Case Report (Pulse, 2014)
Pineal region tumours are rare, even though it gives rise to diverse array of tumour. Among these, pineal parenchymal tumour of intermediate differentiation is a newly recognized entity. We have described a 56 year old male of pineal parenchymal tumour of intermediate differentiation. As this tumour is very rare with uncertain behavior and optimal management, this case report will add value to the existing database. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20356 Pulse Vol.6 January-December 2013 p.60-61